Main outcomes from the IVR code benchmark performed in the European IVMR project. (October 2020) - Carénini, L.; Fichot, F.; Bakouta, N.; Filippov, A.; Le Tellier, R.; Viot, L.; Melnikov, I.; Pandazis, P.
Highlights: A benchmark exercise on IVR was performed covering different configurations. Transient evolutions of the corium pool were considered. Differences in modelling assumptions were identified and discussed. Importance of the kinetics of molten steel incorporation in the pool was shown. Thermochemical equilibrium is considered for oxide and metal phase compositions. Abstract: In-Vessel Retention (IVR) of corium is one of the possible strategies for Severe Accident (SA) mitigation. Its main advantage lies in the fact that, by maintaining the corium within the vessel, it preserves the last containment barrier from corium aggression. One of the issues for the demonstration of the success of this strategy is the evaluation of the behaviour of the corium relocated in the lower head and how it stabilizes and affects the integrity of the vessel wall. The first modelling was developed in the nineties and assessed the heat transfers in a stratified corium pool with a top metal layer made of steel and Zirconium only. About 10 years later, the results of the MASCA program highlighted the possibility of having more complex stratified configurations, including a dense metal layer. Addressing thermochemical effects in the stratification makes the modelling of the corium pool in the lower head more difficult and, in addition, knowledge of the associated kinetics is still limited. As a consequence, available SA codes, either integral or dedicated to the lower head, can differ significantly in their models, which leads to discrepancies in the results when evaluating the IVR strategy. In order to identify the main modelling issues and to assess the capabilities of the codes, a benchmark exercise for code validation was made in the scope of the European H2020 project IVMR (In-Vessel Melt Retention). It is based on the definition of different IVR configurations at reactor scale with an increase in the complexity of the phenomena involved: starting from a steady-state stratified pool with metal on top, up to consideration of corium phase separation at thermochemical equilibrium and progressive ablation of metallic structures and vessel wall. As a last step, the more challenging transient configuration, with formation of a metal layer heavier than the oxide followed later on by stratification inversion, was also studied. It should be noted that mechanical resistance of the ablated vessel wall and cooling conditions out of the RPV in the cavity are not evaluated and considered out of the scope of this benchmark focused on the thermal load transferred from the corium pool through the vessel wall. Six organisations took part in this benchmark (CEA, EDF, GRS, IBRAE, IRSN, NRC-KI) and 6 different codes were used (ASTEC, ATHLET-CD, MAAP_EDF, PROCOR, HEFEST_URAN and HEFEST – stand-alone version of the corresponding module of the SOCRAT code). The main results and outcomes obtained are presented and discussed in this paper. Sensitivity studies have also been performed and allow obtaining a more consolidated range of results. Thanks to this benchmark exercise and to the approach followed with a progressive increase of complexity, the capabilities of codes to evaluate the heat flux profile applied to the vessel wall in steady-state are demonstrated. Then, for transient configurations, it is shown that different modelling approaches give rather consistent results since dispersion remains limited between code predictions, even in the most challenging configuration with stratification inversion: ±40% for the minimum vessel thickness (2.5 cm ± 1 cm). In addition, all codes predict that transient effects lead to more vessel ablation than in the final steady-state. Hence, the importance of the consideration of the progressive molten steel incorporation in the pool and of the consideration of thermochemical equilibrium to calculate the oxide and metal phases composition was highlighted in the benchmark. Regarding the dispersion of the results obtained, analysis shows that uncertainties on metal layer properties have a significant impact. In addition, differences in modelling assumptions were identified and discussed. The main issues are related to the following physical phenomena: (i) The interaction of the oxide crust with the molten steel; (ii) The kinetics of stratification inversion; (iii) The heat transfer in thin metal layer.